Assessment of Intestinal Parasitic Infection and Personal Hygiene Practice Among School Children in A Primary School in A Village in Jakarta, Indonesia - Ika Puspa Sari; Sri Wahdini (Medsci Publications, 2024)
Background: Intestinal parasitic infections (IPI) are still among developing countries' most prevalent parasitic infections. IPI is closely linked to nutrition, personal hygiene, environmental sanitation, income, climate, and education. Aims/Objectives: To assess the IPI and personal hygiene status among school children in the flood-prone area in Jakarta, Indonesia. Methodology: A cross-sectional study was conducted in a government primary school in South Jakarta, Indonesia, involving 157 students. A structured questionnaire was developed to assess the personal hygiene behavior of the students. A physical examination of the nail fingers was conducted as well. Feces samples were collected from each student and examined using direct smear techniques to identify intestinal parasite infection. Results: The prevalence of IPI was 38.2% in single and mixed infections.  Intestinal parasites recorded in this study were Blastocystis hominis, Giardia lamblia, Trichuris trichiura, hookworm eggs, and non-pathogen protozoa Entamoeba coli. There is no significant difference between the prevalence of IPI with footwear usage, nail-cutting once a week (p=0.718), handwashing before the meal (p=0.688), handwashing after defecations (p=0.618); however, there is a significant difference between nail cleanliness and IPI (p=0.003). Conclusions: The prevalence of IPI in these school children was high and required interventions like health education and action on nail and hand hygiene behavior from school personnel or teachers.